2008
DOI: 10.1007/s00299-008-0643-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of proline against cadmium toxicity in micropropagated hyperaccumulator, Solanum nigrum L.

Abstract: Solanum nigrum is a newly discovered Cd-hyperaccumulator. In the present study, the protective effects of proline against cadmium toxicity of callus and regenerated shoots of S. nigrum are investigated based on a high frequency in vitro shoot regeneration system. Proline pretreatment reduces the reactive oxygen species levels and protects the plasma membrane integrity of callus under cadmium stress, and therefore improves the cadmium tolerance in S. nigrum. Inductively coupled plasma mass spectroscopy analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
109
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(119 citation statements)
references
References 35 publications
8
109
1
1
Order By: Relevance
“…However, both of them maintained slightly higher CAT activity in comparison with seedlings treated with Cd alone. Our results are also supported by the results of Xu et al (2009) and Islam et al (2010). Similar effects of proline and betaine on CAT activity were also observed in response to various stresses (Demiral and Türkan 2004;Khedr et al 2003).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, both of them maintained slightly higher CAT activity in comparison with seedlings treated with Cd alone. Our results are also supported by the results of Xu et al (2009) and Islam et al (2010). Similar effects of proline and betaine on CAT activity were also observed in response to various stresses (Demiral and Türkan 2004;Khedr et al 2003).…”
Section: Discussionsupporting
confidence: 90%
“…2a). Increase in GSH content in response to Cd stress were also reported in rice seedlings (Hu et al 2009;Xu et al 2009) and GSH metabolic genes coordinately respond to heavy metal stress (Xiang and Oliver 1998). The increase in GSSG content under Cd stress in the seedlings may partly be attributed to a decreased rate of GSH recycling or an increased rate of its degradation under the conditions of stress Hossain and Fujita 2010).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…121 Proline induces the formation of phytochelatins which chelate with heavy metals like Cd thereby decreasing their toxicity. 122 Xu et al 123 reported that proline pre-treatment reduced the ROS level and also protected the plasma membrane of callus subjected to cadmium stress, thereby improving the cadmium tolerance resulting in regeneration of shoots in Solanum nigrum. Exogenous application of proline resulted in increase of its endogenous levels that antagonized the toxic effects of selenium by improving the growth of seedlings.…”
Section: Effect Of Exogenous Proline On Plants Exposed To Heavy Metalmentioning
confidence: 99%